Impact of Breast Cancer Pathways on ER utilization and hospitalization. Issue 28 (1st October 2022) - Leu, Jane; Doelger, Lisa; Bannister, Wade; Stevens, Erica; Foley, Timothy; Flood, William A.
Abstract : 423 Background :Optum's Cancer Guidance Program promotes value-based care by ensuring that treatments follow evidence-based guidelines and encouraging the use of cancer therapy pathways. Criteria for selection of treatments for pathways include efficacy, toxicity and cost so Pathways could be expected to decrease emergency room utilization and hospitalizations that result from adverse events of therapy. We conducted this study to evaluate the impact of Pathways adherence (on vs. off Pathways) on hospital inpatient and emergency department utilization among commercially insured members with breast cancer. Methods: This cross-sectional matched case-control study used medical claims and prior authorization data to evaluate 12 months of program experience (11/1/2019 – 10/31/2020). Individuals were included if they were 19+ years old, enrolled in the health plan, had actively treated breast cancer (breast cancer diagnosis and 1+ cancer related treatment procedure), and had a cancer drug therapy prior authorization during the study period. On Pathway cases were matched to off Pathway controls with propensity score and outcomes were measured using generalized linear models. The propensity score was estimated using demographic characteristics, cost/utilization preceding the prior authorization request, and clinical indicators (HER2 status, advanced disease, adjuvant vs neoadjuvant therapy, multiple lines of therapy, ECOG /Karnofsky, regimen emetic risk). Outcomes were measured across the member's treatment episode from first month of active cancer treatment to 3 months after last month of active cancer treatment. Results: Compared to those who were off Pathway (n = 1, 001), patients treated with a Pathways regimen (n = 1, 001) had 18% lower (p-value = 0.03) all-cause inpatient admissions, 14% lower (p-value = 0.10) cancer-related inpatient admissions, 18% lower (p-value = 0.11) all-cause emergency department visits, no difference in (p-value = 1.00) cancer-related inpatient bed days, 8% lower (p-value = 0.31) all-cause emergency department visits, and 1% lower (p-value = 0.92) cancer-related emergency department visits. Conclusions: Treatment with a Pathway regimen was associated with fewer all-cause and cancer-related visits to inpatient hospitalizations and fewer all-cause inpatient bed days.